Farm planning with linear programming - Dent, J. B. (John Barry) (Butterworths, 1986)
Farm Planning with Linear Programming: Concept and Practice focuses on concepts and methods in farm planning. The book first discusses the principles of farm planning, including elements of farm planning problems, summary, and review questions. The text highlights farm planning models. The nature of models; commonly used farm planning models; multiple constraint problems and program planning; problems in applying models; and comments are considered. The book also focuses on the linear programming network; opportunity cost and the simplex method; and analysis of the linear programming solution.